Studi Atas Program Pohon Sakramen di Paroki St. Antonius Padua Mbeling dalam Pandangan Eko-Spiritualitas Leonardo Boff - Epin Du, Patrisius; Panggung, Ferdinandus (Perspektif, 2025)
This article aims to examine the Sacrament Tree Program in St. Anthony of Padua Parish, Mbeling, from the perspective of ecotheology, with particular attention to Leonardo Boff’s eco-spirituality. The Sacrament Tree Program forms part of the local Church’s efforts to respond to the ecological crisis while fostering ecological awareness among the faithful in caring for and preserving God’s creation. This study employs a qualitative research design using a phenomenological approach, which focuses on the lived experiences of parishioners and pastoral agents in understanding and implementing the Sacrament Tree Program. Data were collected through interviews and a critical reading of Leonardo Boff’s ecotheological thought. The findings of this study indicate that: (a) the Sacrament Tree Program helps believers to recognize the importance of caring for the environment, affirming that ecological responsibility is an integral dimension of Christian faith and moral commitment; (b) the program serves as an educational medium that fosters a relational ethos and an awareness of the interdependence of all creation; and (c) the program extends beyond an ecological initiative, engaging the spiritual praxis of the faithful and strengthening their commitment to caring for the earth as a common home.